Understanding How Entrepreneurial Leadership Shapes Employees' Innovation Through Employees Intellectual Agility: A Mediation Analysis - Dr. Maryam Hafeez , Dr. Syeda Sana Zainab , Dr. Muahmmad Irfan Sheeraz , Dr. Asad Amjad , Fatima Khan (Migration Letters, 2024)
Entrepreneurial leadership is a significant predictor of employee’s innovative behavior with the mediation of employee’s intellectual agility among information technology sector of Pakistan. This study aims to determine the association between innovative behavior performed by employees and entrepreneurial leadership, while also investigating the mediating functions of employee’s intellectual agility in this relationship. Data were gathered from 295 workers of Pakistani information technology (IT) service companies using a cross-sectional study approach. To test the suggested research model, the partial least squares–structural equation modelling [1](PLS–SEM) technique was used. The results show a strong positive correlation among employees’ innovation and entrepreneurial leadership. Furthermore, this link is simultaneously mediated by employee’s intellectual agility. This study reveals how crucial entrepreneurial leadership is in encouraging innovative behavior among staff members in the IT services sector. The results of this study indicate that managers can improve the abilities of their staff members' intellectual agility by modelling entrepreneurial behaviors. This will encourage staff members to exhibit innovative behavior, which will improve organizational innovation performance. By combining different philosophical perspectives, this study adds something new to the theory of entrepreneurial leadership by presenting a picture of the mechanism which transfer influence of entrepreneurial leadership on innovative work behavior.